Assessment of heavy metals contamination of the water resources in the vicinity of Barapukuria Coal Mine, Phulbari, Dinajpur, NW Bangladesh - Nazmul Haque, Mohammad; H.M. Selim Reza, A.; Kabir, Sohail; Aminul Ahsan, Md.; Saha, Sudip; Akbor, Ahedul (International Journal of Advanced Geosciences, 2020)
The present research work shows that the concentrations of heavy metals can be expressed as Fe>Mn>Zn>Ni>Cr>Pb>Co>As in the groundwater of Phulbari area, Dinajpur, Bangladesh on the basis of their abundance. The Plio-Pleistocene Dupi Tila aquifer sediment is principally composed of quartz, feldspar and lithic grains and is characterized by low ZTR index. Seventeen groundwater samples have higher iron concentrations than the permissible limit of WHO, 2004. The chemical weathering of pyrite release iron in the natural water of the study area. The manganese content of two groundwater samples is higher than the acceptable limit. The high abundance of potassium in 11.11% water samples is indicative of the influence of agricultural activity in the investigated area. The factor analysis reveals the dominance of four factors that comprise 77.276% of the groundwater sample. The contamination index (Cd) for the heavy metals were performed and 88.89% of the groundwater samples have low contamination index. The calcium of the groundwater is resulted from the dissolution of carbonate rocks. The low arsenic concentrations indicate the fast flowing nature of the groundwater and/or low arsenic content of the aquifer sediments. The low cobalt content of the groundwater reflects the low cobalt concentration of the aquifer sediments. The heavy metal chemistry of the groundwater of the study area reveals that the quality of the water is influenced by the geogenic sources as well as the anthropogenic activities like coal mining and agricultural activities.Â Â